Performance and carbon emission of solid waste-based solidification materials cooperative fiber solidifying soil - Benan Shu; Zhi Chen; Guodong Zeng; Maocong Zhu; Keyi Qiu (AIP Advances)
The mechanical and drying shrinkage characteristics of solid waste-based solidification materials (SBM) cooperative fiber solidifying soil were examined. The microstructure was tested using scanning electron microscopy and mercury intrusion porosimetry. The results revealed that the optimum content for both polyvinyl alcohol (PVA) and basalt fiber (BF) was both 0.3%. The uncontrolled compressive strength and deformation modulus (E50) of SBM incorporating PVA were enhanced by 36% and 107%, respectively. At 28 days of curing, the dry shrinkage of solidified soil recycled aggregate showed a reduction of 70%, reaching 300 με. The presence of abundant ettringite (Aft) in SBM solidified soil acted as shrinkage compensatory. The formation of calcium silicate hydrates (CSH) and Aft on the damaged PVA surface suggests that the bonding effect of PVA with the matrix is superior to that of BF. The porosity of SBM solidified soil was diminished to 27%, with the pores shifting toward smaller sizes. The carbon emission and carbon emissions relative to the performance of SBM were 186 kg/t and 50.3 kg/MPa, respectively.